3D modeling of inductive and capacitive coupling between surface‐mounted multilayer‐capacitors. (12th July 2022) - Riener, Christian; Bauernfeind, Thomas; Baumgartner, Paul; Hackl, Herbert; Ibel, Martin; Kvasnicka, Samuel; Prestros, Ralph; Roppert, Klaus; Kaltenbacher, Manfred
Abstract: Electronic based systems (EBS) tend to become smaller in size while at the same time their functionality, complexity, and operating frequencies increase. Therefore, accurate and broadband characterization of the electric behavior of the components of such EBS is becoming more and more important for first‐time right designs, especially for electromagnetic compatibility (EMC) and interference (EMI) issues. Although many of the manufacturers provide the electric characterization of their components up to, for example, 8.5 GHz, there is still a lack of information about the parasitic electromagnetic coupling of their components to others. To characterize this behavior in terms of measurement is demanding due to the small size and the high frequencies, hence the characterization by means of numerical simulations has become popular in the last years. Due to the fact that the components can be quite complex and their structure hard to model and simulate, like it is the case for the here investigated multilayer ceramic capacitors (MLCC), simplified models of the geometry have been typically used. In general, the electromagnetic behavior of multiple components close to each other is of interest, hence numerical efficient models must be deployed to analyze interfering effects toward each other. In the present paper we evaluate different 3D modeling strategies for MLCCs in terms of their capabilities to characterize the mutual coupling between such components.